2013
DOI: 10.1175/jcli-d-12-00124.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ENSO on the Diurnal Cycle of Rainfall over the Maritime Continent and Australia

Abstract: This study examines the influence of ENSO on the diurnal cycle of rainfall during boreal winter for the period 1998–2010 over the Maritime Continent (MC) and Australia using Tropical Rainfall Measuring Mission (TRMM) and reanalysis data. The diurnal cycles are composited for the ENSO cold (La Niña) and warm (El Niño) phases. The k-means clustering technique is then applied to group the TRMM data into six clusters, each with a distinct diurnal cycle. Despite the alternating patterns of widespread large-scale su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 69 publications
6
43
1
Order By: Relevance
“…Using an objective pattern recognition technique Bergemann et al [] showed that in coastal regions of the tropics, in particular over the many islands of the Maritime Continent, coastally influenced rainfall constitutes more than a third of the overall annual rainfall received, indicating its importance for the region and its likely strong effect on the large‐scale circulation through convective heating effects [ Neale and Slingo , ]. Several recent studies [ Rauniyar and Walsh , , ; Peatman et al , ; Bergemann et al , ] have presented evidence that the rainfall characteristics of large‐scale tropical circulations, such as the Madden‐Julian Oscillation (MJO) [ Madden and Julian , , , ], are strongly modified by the presence of coasts. They showed that in the coastal regions of the Maritime Continent, rainfall is strongly modulated by coastline effects leading to enhanced precipitation in the suppressed MJO phase and therefore very small differences in rainfall between active and suppressed MJO conditions over the land regions of the Maritime Continent.…”
Section: Introductionmentioning
confidence: 99%
“…Using an objective pattern recognition technique Bergemann et al [] showed that in coastal regions of the tropics, in particular over the many islands of the Maritime Continent, coastally influenced rainfall constitutes more than a third of the overall annual rainfall received, indicating its importance for the region and its likely strong effect on the large‐scale circulation through convective heating effects [ Neale and Slingo , ]. Several recent studies [ Rauniyar and Walsh , , ; Peatman et al , ; Bergemann et al , ] have presented evidence that the rainfall characteristics of large‐scale tropical circulations, such as the Madden‐Julian Oscillation (MJO) [ Madden and Julian , , , ], are strongly modified by the presence of coasts. They showed that in the coastal regions of the Maritime Continent, rainfall is strongly modulated by coastline effects leading to enhanced precipitation in the suppressed MJO phase and therefore very small differences in rainfall between active and suppressed MJO conditions over the land regions of the Maritime Continent.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that the tropical Pacific sea surface temperature (SST) is one of the important factors influencing the variability of precipitation over the Maritime Continent (Lau and Chang, 1987;Wang et al, 2000Wang et al, , 2003Wu et al, 2003;Chang et al, 2004;Feng et al, 2010;Qian et al, 2010;Wang and Chen, 2010;Chen et al, 2013aChen et al, , 2013bRauniyar and Walsh, 2013;Smith et al, 2013). The processes through which the tropical Pacific SST influences climate variation over the Maritime Continent (Zhang et al, 1996;Chang et al, 2000;Wang et al, 2000;Feng et al, 2010;Wu et al, 2010) and the East Asian region (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This trend is different from our data of dry mid Holocene and wet late Holocene in spite of regional proximity. However, their vegetation reconstruction represented mainly those of low altitude plain in nearby Island, and recent modeling study (Qian et al, 2010) and meteorological data (Rauniyar and Walsh, 2013) in Indonesian islands observed large decrease of wet season rainfall in El Niño years in low altitude plains or oceanic area, whereas it increased in mountainous area due to local changes of wind directions and orographic convergence effect on atmospheric circulation. In view of this, local altitudinal difference could be the cause of the opposite rainfall trends.…”
Section: Regional Comparisonmentioning
confidence: 99%
“…Terrestrial lacustrine deposits have potential to show more immediate data of rainfall variations that are most concerned issues for socioeconomics, but more numbers of sedimentary records are necessary as they are often discontinuous due to frequent episodic sedimentation events (Pirrung et al, 2004(Pirrung et al, , 2005Rodysill et al, 2012). Terrestrial archives could be also influenced by local climate features related to configuration of islands and regional topography (Rauniyar and Walsh, 2013;Dubois et al, 2014).…”
Section: Introductionmentioning
confidence: 99%